Customer satisfaction survey in Friuli Venezia Giulia university canteens. (13th November 2019) - Perri, G; Righini, M; Tullio, A; Del Pin, M; Maifreni, M; Marino, M; Fedele, M C; Parpinel, M
Abstract: Background: Customer satisfaction represents an innovative approach to measure strengths and weaknesses of an organization and is useful for a customer-focused management and culture development. Our survey's aim was to investigate perceived quality and needs of customers in the university canteen sector. Methods: Between April and June 2018, an anonymous online questionnaire was distributed by "agenzia regionale per il diritto agli studi superiori" (ARDISS) among university students in Friuli Venezia Giulia, Italy. The questions covered 3 thematic areas: attendance of the service, quality of services and opinions on new initiatives. Furthermore, there was an open question to collect students' suggestions or proposals to improve the service. Satisfaction about the service was evaluated through five topics: environments, hygiene, staff, meals, global satisfaction. Collected data were analyzed with descriptive, univariate and multivariate analyses. Statistical analyses were performed using 9.4 SAS software. Results: Response rate was 20.5% (1933/9404). Multiple logistic regression analyses showed a difference in meal choice (entire vs reduced) between institutional canteen and partner cafeterias users (p < 0.0001) and that male (p < 0.0001) and foreign students (p 0.0003) prefer entire meal instead of reduced. Percentage of students who prefer entire meal is reduced (p < 0.0001) if price range increases. Univariate and multivariate analyses showed that high quality perception is associated with lower price range and no suggestions about food and environments (p < 0.0001); multivariate analyses also showed an association between high quality perception and high canteen attendance (p < 0.05). Conclusions: The survey showed an association between meal choice and students' profile and between perceived quality and customer's features. These data and further analyses may help to select areas where an intervention could improve service quality and, therefore, customer satisfaction. Key messages: Customer satisfaction is an important tool to measure and improve university canteen service quality. These results helped us to identify services' strengths and weaknesses according to students' opinions; this could be useful to select improvement areas.